Immunotherapy associated Sweet syndrome in a patient with metastatic melanoma: A case report - Rory Barry; Gregg Murray; Sally McGrath; Clive Kilgallen; Karen Eustace (Wiley, 2024)
Abstract Immunotherapy agents are now widely used in the treatment of metastatic melanoma. Immune‐related adverse events (irAEs) may occur, including cutaneous pathologies in 50% of patients. We report a case of Sweet syndrome (SS) in a patient who was prescribed ipilimumab and nivolumab for metastatic melanoma.